Cytopathology Practice in the COVID-19 Era: Focus on Sample Workload - Antonino Iaccarino; Filippo Dello Iacovo; Pasquale Pisapia; Caterina De Luca; Umberto Malapelle; Claudio Bellevicine; Giancarlo Troncone; Elena Vigliar (MDPI AG, 2021)
Since the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) outbreak was declared a pandemic, the magnitude of coronavirus disease 2019 (COVID-19) has continued to grow, putting an unprecedented strain on all medical fields. Its effects on cytopathology workloads have been dramatic. Indeed, despite the implementation of several laboratory biosafety recommendations, cytological screening activities and cytological sampling of patients at low risk of malignancy have been postponed to limit the risk of contagion and to lessen the strain on overwhelmed hospital facilities. In this scenario, a drastic reduction in the total number of cytological specimens has been observed worldwide. This review summarizes the current evidence of the impact of the COVID-19 pandemic on cytopathology practice by focusing on its impact on cytological sample workload.